Locoregional and free flap reconstruction of the lateral skull base. Issue 9 (23rd August 2014) - Richmon, Jeremy D.; Yarlagadda, Bharat B.; Wax, Mark K.; Patel, Urjeet; Diaz, Jason; Lin, Derrick T.; Eisele, David W.
Abstract Lateral temporal bone reconstruction after ablative surgery for malignancy, chronic infection, osteoradionecrosis, or trauma presents a challenge for the reconstructive surgeon. This complexity is due to the 3D nature of the region, potential dural exposure, and the possible need for external surface repair. Successful reconstruction therefore requires achieving separation of the dura, obliteration of volume defect, and external cutaneous repair. There is significant institutional bias on the best method of reconstruction of these defects. In this review, the advantages and disadvantages of reconstructive options will be discussed as well as the potential pitfalls and complications. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1387–1391, 2015